Hepatitis A in Central Argentina: Anti-HAV prevalence in adults living in a region of low endemicity 17 years after the official introduction of the vaccine - Castro, Gonzalo Manuel (2025)
Hepatitis A virus (HAV) has a low endemic circulation pattern in Argentina. Clinical cases mainly occurred in susceptible young adults, with recent outbreaks reported. The aim of this study was to provide updated information on the HAV immune status of the adult population from Central Argentina. A retrospective analysis was conducted, recording the results of anti-HAV IgG in 4235 samples of individuals without prior vaccination from Córdoba, Argentina (2019 and 2022). Epidemiological data recorded included sex, age, HIV status and income level. The overall prevalence of anti-HAV was 70.1%, increasing with age as follows: 52.6% among the 18–25-year-old group, 53.8% in 26–35-year-old young adults, 67.4% in 36–45-year old adults, and >80% in the >46-year-old group. Moreover, prevalence was associated with low-income populations and was significantly higher among female patients (p<0.0001). Considering the high proportion of young adult individuals susceptible to HAV infection identified, along with evidence of HAV circulation in the region – which can be easily introduced by unvaccinated immigrants or travelers from medium/high endemic countries – and the existence of a safe, efficient vaccine, we strongly recommend further investigating HAV immunity in individuals over 18 years old in our region. For those testing negative, vaccination is recommended.